2006
DOI: 10.1111/j.1551-2916.2006.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Sintering of Zn3Nb2O8 Ceramics from Fine Powders

Abstract: A possibility to produce microwave (MW) dielectric materials by liquid‐phase sintering of fine particles was investigated. Zn3Nb2O8 powders with a grain size 50–300 nm were obtained by the thermal decomposition of freeze‐dried Zn–Nb hydroxides or frozen oxalate solutions. The crystallization of Zn3Nb2O8 from amorphous decomposition products was often accompanied by the simultaneous formation of ZnNb2O6. Maximum sintering activity was observed for single‐phase crystalline Zn3Nb2O8 powders obtained at the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Variation of the thermal processing conditions allows modification of the micromorphology of the particles thus formed, and ensures the maximum sinterability of oxide powders in order to obtain dense functional ceramics at the lowest possible temperatures [56,57]. The absence of hard agglomerates in the starting powder is crucial for the production of optically transparent, fully dense ceramics [33] that can be used as the active body of solid state lasers instead of single crystals [58][59][60].…”
Section: Precipitated and Co-precipitated Cryogelsmentioning
confidence: 98%
“…Variation of the thermal processing conditions allows modification of the micromorphology of the particles thus formed, and ensures the maximum sinterability of oxide powders in order to obtain dense functional ceramics at the lowest possible temperatures [56,57]. The absence of hard agglomerates in the starting powder is crucial for the production of optically transparent, fully dense ceramics [33] that can be used as the active body of solid state lasers instead of single crystals [58][59][60].…”
Section: Precipitated and Co-precipitated Cryogelsmentioning
confidence: 98%
“…Liquid phase-assisted sintering of single phase Zn 3 Nb 2 O 8 powders, obtained from coprecipitated precursors, at T = 740-780 • C allows to obtain microwave dielectric ceramics with 94-95% density, ε r = 20.2-20.8 and Q × F = 30 000-36 000 GHz. Further optimization of powder synthesis and processing conditions allowed to reduce the sintering temperature of Zn 3 Nb 2 O 8 ceramics down to 680 • C [20].…”
Section: Binbomentioning
confidence: 99%
“…Taking into account that the formation of ZnNb 2 O 6 is kinetically preferable, the synthesis of Zn 3 Nb 2 O 8 powders with T s < 800 • C requires a careful optimization of processing conditions. More detailed discussion of the Zn 3 Nb 2 O 8 formation from freeze dried precursors can be found elsewhere [20].…”
Section: Binbomentioning
confidence: 99%
“…Interesting feature observed during these studies dealt with maximum sintering activity that was never observed for the powders with minimum grain size. Simultaneous promotion of the intensive grain growth during sintering allowed to produce microwave dielectric materials with Q Â F ¼ 20000 À 35000 GHz [101][102][103].…”
Section: Dense Ceramic Materials From Cryogel Precursorsmentioning
confidence: 99%